The Impact of Sleep Disruption on Complex Cognitive Tasks: A Meta-Analysis. (September 2015) - Wickens, Christopher D.; Hutchins, Shaun D.; Laux, Lila; Sebok, Angelia
Objective: We aimed to build upon the state of knowledge about the impacts of sleep disruption into the domain of complex cognitive task performance for three types of sleep disruption: total sleep deprivation, sleep restriction, and circadian cycle. Background: Sleep disruption affects human performance by increasing the likelihood of errors or the time it takes to complete tasks, such as the Psychomotor Vigilance Task. It is not clear whether complex tasks are affected in the same way. Understanding the impact of sleep disruption on complex cognitive tasks is important for, and in some instances more relevant to, professional workers confronted with unexpected, catastrophic failures following a period of disrupted sleep. Method: Meta-analytic review methods were applied to each of the three different areas of sleep disruption research. Results: Complex cognitive task performance declines over consecutive hours of continuous wakefulness as well as consecutive days of restricted sleep, is worse for severely restricted sleep (4 or fewer hours in bed), is worse during the circadian nadir than apex, and appears less degraded than simple task performance. Conclusion: The reviews suggest that complex cognitive task performance may not be impacted by disrupted sleep as severely as simple cognitive task performance. Application: Findings apply to predicting effects of sleep disruption on workers in safety-critical environments, such as health care, aviation, the military, process control, and in particular, safety-critical environments involving shiftwork or long-duration missions.